Effect of Sodium‐Glucose Cotransport‐2 Inhibitors on Blood Pressure in People With Type 2 Diabetes Mellitus: A Systematic Review and Meta‐Analysis of 43 Randomized Control Trials With 22 528 Patients. Issue 6 (25th May 2017) - Mazidi, Mohsen; Rezaie, Peyman; Gao, Hong‐Kai; Kengne, Andre Pascal
Abstract : Background: The sodium‐glucose cotransporter 2 (SGLT2) inhibitors are a class of oral hypoglycemic agents. We undertake a systematic review and meta‐analysis of prospective studies to determine the effect of SGLT2 on blood pressure (BP) among individuals with type 2 diabetes mellitus. Methods and Results: PubMed‐Medline, Web of Science, Cochrane Database, and Google Scholar databases were searched to identify trial registries evaluating the impact of SGLT2 on BP. Random‐effects models meta‐analysis was used for quantitative data synthesis. The meta‐analysis indicated a significant reduction in systolic BP following treatment with SGLT2 (weighted mean difference −2.46 mm Hg [95% CI −2.86 to −2.06]). The weighted mean differences for the effect on diastolic BP was −1.46 mm Hg (95% CI −1.82 to −1.09). In these subjects the weighted mean difference effects on serum triglycerides and total cholesterol were −2.08 mg/dL (95% CI −2.51 to −1.64) and 0.77 mg/dL (95% CI 0.33‐1.21), respectively. The weighted mean differences for the effect of SGLT2 on body weight was −1.88 kg (95% CI −2.11 to −1.66) across all studies. These findings were robust in sensitivity analyses. Conclusions: Treatment with SGLT2 glucose cotransporter inhibitors therefore has beneficial off‐target effects on BP in patients with type 2 diabetes mellitus and may also be of value in improving other cardiometabolic parameters including lipid profile and body weight in addition to their expected effects on glycemic control. However, our findings should be interpreted with consideration for the moderate statistical heterogeneity across the included studies.